Power storage equipment
By using hindered phenol compounds in the elastic members of the power storage equipment, the problem of thermal deterioration of the elastic members under high temperature environment is solved, and the effect of effectively suppressing thermal deterioration and preventing cracks is achieved.
Patent Information
- Application Number
- CN202211283201.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-09-29
- Filing Date
- 2018-09-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2038-09-28
AI Technical Summary
In a high temperature environment, the elastic members in the existing power storage equipment are prone to thermal deterioration and are difficult to effectively suppress.
The hindered phenol compound is added to the elastic member. The hindered phenol compound has a specific hindered group structure in the phenol skeleton, and can inhibit the oxidation and deterioration of the elastic polymer at high temperature.
By using the hindered phenol compound, thermal deterioration of the elastic member can be effectively suppressed, cracks can be prevented, and sealing properties can be maintained even in a high temperature environment.
Smart Images

Figure CN115483035B_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of September 28, 2018, application number 201880061655.6, and invention name “Electricity Storage Device”. Technical Field
[0002] The present invention relates to an electric storage device using a sealing member including an elastic member. Background Art
[0003] An electrolytic capacitor, which is a type of electrical storage device, includes a capacitor element, a housing for housing the capacitor element, and a sealing member for sealing an opening of the housing. The sealing member includes an elastic member embedded in the opening of the housing, and the elastic member is made of an elastic material such as rubber or a rubber-like polymer. Additives such as fillers, vulcanizers, reinforcing agents, and anti-aging agents are sometimes added to the elastic member (Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 11-274011 Summary of the invention
[0007] Problems to be solved by the invention
[0008] When the electric storage device is used in a high temperature environment, thermal degradation of the elastic member becomes significant. It is difficult to sufficiently suppress thermal degradation of conventional elastic members.
[0009] Methods used to solve problems
[0010] One aspect of the present invention relates to an electric storage device comprising an electric storage element, a housing having an opening and accommodating the electric storage element, and a sealing member for sealing the opening, wherein the sealing member comprises an elastic member embedded in the opening, the elastic member comprising an elastic polymer and a hindered phenol compound, wherein the hindered phenol compound has a first hindered group and a second hindered group at a first substitution position and a second substitution position adjacent to a phenolic hydroxyl group in a phenol skeleton, respectively, the first hindered group and the second hindered group each comprising at least one tertiary carbon, and one of the tertiary carbons of the first hindered group and the second hindered group is bonded to the first substitution position and the second substitution position, respectively.
[0011] Effects of the Invention
[0012] In the power storage device, thermal degradation of the elastic member can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1It is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention.
[0014] Figure 2 It is a schematic diagram for explaining the structure of the capacitor element of the same embodiment. DETAILED DESCRIPTION
[0015] An electrolytic capacitor as a type of storage device according to one embodiment of the present invention comprises a capacitor element as a type of storage element, a housing having an opening and accommodating the capacitor element, and a sealing member for sealing the opening. The sealing member comprises an elastic member embedded in the opening. The elastic member comprises an elastic polymer and a hindered phenol compound. For the hindered phenol compound, in the phenol skeleton, a first hindered group and a second hindered group are respectively provided at the first substitution position and the second substitution position adjacent to the phenolic hydroxyl group. The first hindered group and the second hindered group each comprise at least one tertiary carbon, and with respect to the first hindered group and the second hindered group, one of the tertiary carbons is bonded to the first substitution position and the second substitution position, respectively.
[0016] Electrolytic capacitors are sometimes conceived to be used in high-temperature environments such as in the engine room of a car. The opening of the housing that accommodates the capacitor element is sealed by embedding an elastic member. Since the elastic member is composed of an organic polymer such as rubber, the heat resistance is insufficient and oxidative degradation occurs in a high-temperature environment. Specifically, in a high-temperature environment, due to the action of heat, free radicals are generated from the organic polymer that constitutes the elastic member, and oxygen is added, and the adduct further converts the organic polymer into free radicals. During the repetition of these processes, the polymer chain of the organic polymer becomes shorter. Since the shortened organic polymer evaporates due to the action of heat, the elastic member becomes brittle. When an anti-aging agent is added to the elastic member, proton free radicals are supplied from the anti-aging agent, so the free radicals of the organic polymer can be captured and oxidative degradation can be suppressed. However, in a high-temperature environment, the anti-aging agent volatilizes, and the sufficient free radical capture effect brought by the anti-aging agent cannot be obtained, and it is difficult to suppress the thermal degradation of the elastic member.
[0017] In addition, in an electrolytic capacitor, when the capacitor element is housed in a case and sealed, a large stress is applied to the elastic member because an elastic member is embedded in the opening of the case. When the elastic member is subjected to stress, if the elastic member is thermally degraded, cracks are likely to occur.
[0018] According to the above-mentioned embodiment of the present invention, by using a specific hindered phenol compound in the elastic member, the oxidative degradation of the elastic polymer constituting the elastic member can be suppressed even in a high temperature environment. Thus, the thermal degradation of the elastic member can be suppressed. Since the thermal degradation is suppressed, even in a state where stress is applied to the elastic member due to sealing, the generation of cracks in the elastic member can be suppressed.
[0019] Hereinafter, the present invention will be described in more detail based on the embodiments. However, the following embodiments do not limit the present invention.
[0020] Figure 1 is a schematic cross-sectional view of an electrolytic capacitor according to this embodiment, Figure 2 This is a schematic diagram showing a portion of a capacitor element of the same electrolytic capacitor being developed.
[0021] The electrolytic capacitor includes, for example, a capacitor element 10, a cylindrical housing 11 accommodating the capacitor element 10, a sealing member composed of an elastic member 12 for sealing an opening of the housing 11, a seat plate 13 facing the elastic member 12, leads 14A and 14B extending from a through hole 12a of the elastic member 12 and penetrating the seat plate 13, and lead tabs 15A and 15B connecting the leads to electrodes of the capacitor element 10. The vicinity of the opening end of the housing 11 is drawn inward, and the opening end is curled in a manner pressed against the elastic member 12. In addition, a region 11a in which the housing 11 is reduced in diameter by drawing (specifically, transverse drawing) is formed in a portion of the housing 11 facing the side wall of the elastic member 12.
[0022] The capacitor element 10 is composed of Figure 2 The wound body is produced as shown. The wound body includes an anode portion 21 connected to the lead tab 15A, a cathode portion 22 connected to the lead tab 15B, and a separator 23. Figure 2 The jellyroll shown in FIG. 1 is a semi-finished product without electrolyte.
[0023] The anode portion 21 and the cathode portion 22 are wound with a separator 23 interposed therebetween. The outermost periphery of the wound body is fixed by a winding fixing tape 24. It should be noted that Figure 2 The diagram shows a partially unfolded state before the outermost circumference of the wound body is fixed.
[0024] The anode portion 21 is provided with a metal foil having a roughened surface and having a concavo-convex surface, and a chemical treatment film is formed on the metal foil having the concavo-convex surface. In the capacitor element 10, a solid electrolyte is attached to at least a portion of the surface of the chemical treatment film. The solid electrolyte can cover at least a portion of the surface of the cathode portion 22 and / or the surface of the spacer 23. The capacitor element 10 formed with the solid electrolyte is accommodated in the housing 11, and the opening of the housing 11 is sealed with a sealing member, thereby making an electrolytic capacitor. When an electrolyte is used, the electrolyte is accommodated in the housing 11 together with the capacitor element 10.
[0025] (Sealing member)
[0026] The sealing member includes an elastic member 12, and seals the opening of the case accommodating the capacitor element 10 in a state where the elastic member 12 is fitted into the opening of the case accommodating the capacitor element 10. The elastic member 12 contains an elastic polymer and a hindered phenol compound.
[0027] As the elastic polymer, an insulating elastic polymer is used. Examples of the elastic polymer include butyl rubber, isoprene rubber, silicone rubber, fluororubber, ethylene propylene rubber, chlorosulfonated polyethylene rubber (Hypalon rubber, etc.), etc. The elastic polymer may be used alone or in combination of two or more.
[0028] The hindered phenol compound has a first hindered group and a second hindered group at two substitution positions (the first substitution position and the second substitution position) adjacent to the phenolic hydroxyl group in the phenol skeleton. These hindered groups each contain at least one tertiary carbon, and in each hindered group, one of the tertiary carbons is bonded to the above-mentioned substitution position, becoming a quaternary carbon in the hindered phenol compound. Specifically, one of the tertiary carbons of the first and second hindered groups is directly bonded to the first substitution position and the second substitution position, respectively. Compared with the case where a hydrogen atom or a primary carbon or secondary carbon of a substituent is bonded to the first substitution position or the second substitution position, the hindered phenol compound of this structure has high heat resistance, and decomposition can be suppressed even at high temperatures (e.g., 155°C), with basically no mass change. Therefore, even in a high temperature environment, the hindered phenol compound remains in the elastic member, exerting a free radical capture function, so that thermal degradation of the elastic polymer can be suppressed. Thus, even if the elastic member 12 is exposed to a high temperature environment while being stressed by being pressed by the open end of the housing or being stressed by drawing the housing, the occurrence of cracks can be suppressed.
[0029] The first and second hindered groups are respectively substituents with large steric hindrance, and may contain at least one tertiary carbon, or may contain two or more tertiary carbons. Examples of each hindered group include tert-butyl, 1,1-dimethyl-propyl, mesityl, etc. From the viewpoint of easily obtaining a hindered phenol compound and obtaining a high thermal degradation inhibition effect, it is preferred that both the first and second hindered groups are tert-butyl.
[0030] The hindered phenol compound contained in the elastic member 12 can be identified, for example, by extracting the elastic member 12 with a solvent (such as acetone) under heating (for example, at 80° C.) using a Soxhlet extractor, and subjecting the obtained extract to gas chromatography-mass spectrometry (GC-MS analysis). It should be noted that compounds with relatively high molecular weight can be identified by liquid chromatography-mass spectrometry (LC-MS analysis) instead of GC-MS analysis.
[0031] The molecular weight of the hindered phenol compound is preferably 300 to 3000, more preferably 400 to 2000 or 450 to 1500. The hindered phenol compound having a molecular weight in this range is not only easy to disperse uniformly, but also has little mass change at high temperature (e.g., 155° C.). Since the mass change at high temperature is small, even if the elastic member 12 is exposed to a high temperature environment, it will not volatilize, and can exert an anti-aging effect, further improving the effect of suppressing thermal degradation of the elastic member 12.
[0032] The molecular weight can be determined by GC-MS analysis or LC-MS analysis. For compounds with a relatively high molecular weight, the average molecular weight (weight average molecular weight) may be within the above-mentioned molecular weight range.
[0033] If the hindered phenol compound is easy to generate proton radicals, the effect of capturing the radicals generated from the elastic polymer is improved. The more stable the phenol radical generated by removing the proton radical from the hindered phenol compound, the easier it is to generate the proton radical. In this case, the effect of suppressing the thermal degradation of the elastic polymer is improved. From this point of view, the heat of reaction of the phenol radical generation of the hindered phenol compound is preferably 82 kcal / mol (≈343 kJ / mol) or less, more preferably 81 kcal / mol (≈339 kJ / mol) or less or 80 kcal / mol (≈335 kJ / mol) or less.
[0034] In addition, the heat of reaction (Hr) of phenol radical generation of the hindered phenol compound was calculated by the following formula.
[0035] Hr(kcal / mol)=E r -(E0+E p )
[0036] (Where, E r is the energy of the free radical state of the hindered phenol compound, E0 is the energy of the state before the hindered phenol compound becomes a free radical, and E p is the energy of the proton free radical. )
[0037] E r , E0, and E pThe energies of are obtained by density functional method. In the calculation of density functional, Gaussian09, Revision E.01, a first principle molecular orbital method calculation program made by Gaussian, is used. As a density functional, the B3LYP density functional proposed by Becke, Lee, Yang, and Parr (AD Becke, J. Chem. Phys. 98 (1993) 5648; C. Lee, W. Yang, RG Parr, Phys. Rev. B 37 (1988) 785) is used. As a basis function, the 6-31G * basis function (R. Ditchfield, WJ Hehre, and JA Pople, J. Chem. Phys., 54 (1971) 724.) is used. It should be noted that the energy of the free radical in the open shell state uses the value based on the restricted open shell method.
[0038] The unit Ha of each energy was converted into kcal / mol to determine the stabilization energy.
[0039] Examples of the hindered phenol compound include pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate], octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)mesitylene, 1,3,5-tris[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and 2,2'-thiodiethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
[0040] The hindered phenol compound may be used alone or in combination of two or more.
[0041] The amount of the hindered phenol compound contained in the elastic member 12 is preferably 0.5 parts by mass or more and 6.0 parts by mass or less, and more preferably 0.5 parts by mass or more and 4.0 parts by mass or less, relative to 100 parts by mass of the elastic polymer. When the amount of the hindered phenol compound is within this range, the free radical scavenging effect brought about by the hindered phenol compound is easily exerted, and the effect of suppressing the thermal degradation of the elastic member 12 can be further improved. In addition, it is easy to ensure appropriate hardness, and it can be suppressed that the elastic member 12 expands during reflow or that vulcanization is inhibited when the elastic member 12 is formed.
[0042] The elastic member 12 may further include a filler. As fillers, talc, mica, silica, kaolin, titanium dioxide, and / or aluminum oxide can be cited. The amount of the filler contained in the elastic member is preferably, for example, 10 parts by mass or more, and more preferably 50 parts by mass or more relative to 100 parts by mass of the elastic polymer. Thus, even if the elastic member 12 is exposed to a high temperature environment, the generation of cracks can be suppressed. The amount of the filler contained in the elastic member is preferably, for example, 120 parts by mass or less, and more preferably 100 parts by mass or less relative to 100 parts by mass of the elastic polymer. Thus, it is easy to ensure moderate hardness in the elastic member 12, it is easy to ensure a high sealing function and suppress the reduction of the airtightness of the electrolytic capacitor, and it is possible to suppress the reduction of the yield rate during assembly. These lower limits and upper limits can be combined arbitrarily.
[0043] If talcum is used as a filler, the crosslinking of the elastic polymer is promoted, so the thermal degradation of the elastic polymer can be more effectively suppressed. The amount of talcum contained in the elastic member is, for example, more than 10 mass parts relative to 100 mass parts of the elastic polymer, more preferably more than 50 mass parts or more than 50 mass parts, and particularly preferably more than 70 mass parts or more than 80 mass parts. When the amount of talcum is such a range, the crosslinking promotion effect of the elastic polymer is easy to improve, which is more effective in suppressing the thermal degradation of the elastic polymer. The amount of talcum relative to 100 mass parts of the elastic polymer is, for example, less than 120 mass parts or less than 100 mass parts. These lower limits and upper limits can be combined arbitrarily.
[0044] In addition, the elastic member 12 may contain additives (reinforcers (carbon black, etc.), crosslinking agents, crosslinking accelerators, dispersing aids, modifiers, vulcanizing agents, vulcanization aids, and / or processing aids, etc.) as necessary.
[0045] The elastic member 12 has a shape (eg, a disk shape, etc.) corresponding to the shape of the opening of the housing 11. The opening end is curled and directly or indirectly pressed against the elastic member 12 to seal the opening of the housing 11.
[0046] The elastic member 12 is formed in a manner to block the opening of the housing 11. The elastic member 12 is generally provided with a through hole 12a through which a wire is passed. The wire includes lead wires 14A, 14B and lead terminals 15A, 15B for extracting current from the capacitor element 10. In the through hole 12a portion, since it is necessary to prevent a gap between the elastic member 12 and the wire, the area around the through hole 12a of the elastic member 12 is pressed by the wire and subjected to stress. For this reason, in general, such an elastic member having a through hole is prone to cracking in a high temperature environment. In this embodiment, by containing the hindered phenol compound as described above in the elastic member 12, thermal degradation of the elastic polymer can be suppressed, so even in the case where the elastic member 12 has a through hole 12a, the generation of cracks can be suppressed.
[0047] The sealing member may be composed of only the elastic member 12, or may include other members in addition to the elastic member 12. For example, the elastic member may have a resin layer formed on the outer surface. In this case, the sealing member includes the elastic member and the resin layer.
[0048] (Housing 11)
[0049] As the material of the shell 11 for accommodating the capacitor element 10, for example, metals such as aluminum, stainless steel, copper, iron, brass, or their alloys can be cited. After accommodating the capacitor element 10, the opening of the shell 11 is sealed by a sealing member. The shell 11 is a cylindrical shape such as a cylinder, and may also have a bottom as shown in the example in the figure. When using a bottomed shell, one opening can be sealed with a sealing member. In addition, when the two ends of the cylindrical shell (i.e., the two ends of the length direction (or axial direction) of the cylindrical shell) are open, the two openings can be sealed with a sealing member.
[0050] After the capacitor element 10 is accommodated in the housing 11 and the elastic member 12 of the sealing member is embedded in the opening of the housing 11, the housing 11 becomes a state of shrinking and pressing against the side wall of the elastic member 12. By means of this shrinking, the sealing member is fixed, and the airtightness between the elastic member 12 and the side wall of the housing 11 can be improved. The shrinking can be performed by drawing (specifically, transverse drawing) the side wall of the tubular housing 11 from the outside relative to the elastic member 12. Stress is applied to the elastic member 12 due to the shrinking. When the elastic member 12 is exposed to high temperature under the stress, the thermal degradation of the elastic member 12 becomes significant. In the present embodiment, even in the case where the elastic member 12 is easily stressed due to the shrinking, the thermal degradation of the elastic polymer is suppressed because the elastic member 12 contains the hindered phenol compound as described above, so the generation of cracks can be suppressed.
[0051] It should be noted that, in the portion where the elastic member 12 is embedded, when the outer shell 11 is reduced in diameter relative to the side wall of the elastic member 12, the outer diameter of the outer shell 11 becomes smaller than other portions in the reduced diameter region 11a. In the portion of the elastic member 12 corresponding to the side wall, the region where the outer diameter of the outer shell 11 becomes smaller than other portions is set as the reduced diameter region.
[0052] (Capacitor element 10)
[0053] Capacitor element 10 (electricity storage element) includes an anode portion having a dielectric layer (chemical treatment film), a cathode portion, a separator interposed between the anode portion and the cathode portion, and an electrolyte in contact with the dielectric layer.
[0054] (Anode)
[0055] As the anode portion, for example, a metal foil or a metal sintered body with a roughened surface can be cited. The type of metal constituting the anode portion is not particularly limited, but from the point of view of facilitating the formation of a dielectric layer, preferably a valve metal such as aluminum, tantalum, niobium, titanium, or an alloy containing a valve metal is used.
[0056] The surface of the metal foil can be roughened by a known method. By roughening, a plurality of concavities and convexities are formed on the surface of the metal foil. The roughening is preferably performed by etching the metal foil, for example. The etching process can be performed by direct current electrolysis or alternating current electrolysis.
[0057] (Dielectric layer)
[0058] The dielectric layer is formed on the surface of the anode portion. Specifically, since the dielectric layer is formed on the roughened surface of the metal foil, it is formed along the inner wall surface of the holes and depressions (pits) on the surface of the anode portion.
[0059] The formation method of the dielectric layer is not particularly limited, and the dielectric layer can be formed by subjecting the anode portion to a chemical conversion treatment. The chemical conversion treatment can be performed, for example, by immersing the metal foil in a chemical conversion solution such as an ammonium adipate solution. During the chemical conversion treatment, a voltage can be applied to the metal foil while it is immersed in the chemical conversion solution as required.
[0060] Generally, from the viewpoint of mass productivity, a large sheet of metal foil formed of a valve metal or the like is subjected to a roughening treatment and a chemical conversion treatment. In this case, the treated foil is cut into a desired size to prepare an anode portion having a dielectric layer formed thereon.
[0061] (Cathode)
[0062] As the cathode portion, for example, a metal foil can be used. The type of metal is not particularly limited, and preferably a valve metal such as aluminum, tantalum, niobium, or an alloy containing a valve metal is used. As required, the cathode portion can be roughened and / or chemically treated. Roughening and chemically treating can be performed, for example, using the methods described for the anode portion.
[0063] (Spacer)
[0064] The separator is not particularly limited, and for example, nonwoven fabrics containing fibers of cellulose, polyethylene terephthalate, vinylon, or polyamide (for example, aliphatic polyamide, aromatic polyamide such as aramid) can be used.
[0065] The capacitor element can be made by a known method. For example, the capacitor element can be made by overlapping an anode portion and a cathode portion with a dielectric layer formed thereon with a spacer interposed therebetween, and then forming a conductive polymer layer between the anode portion and the cathode portion. Alternatively, the capacitor element can be made by winding an anode portion and a cathode portion with a dielectric layer formed thereon with a spacer interposed therebetween. Figure 2 The wound body shown in FIG. 1 is made by forming a conductive polymer layer between the anode portion and the cathode portion. When forming the wound body, the lead terminals 15A and 15B can be wound while being wound, and the wound body can be formed as shown in FIG. Figure 2 The leads 14A, 14B are shown standing upright from the wound body.
[0066] The outermost part of the anode part, cathode part and separator ( Figure 2 The end of the outer surface of the cathode portion 22 is fixed by a winding fixing tape. It should be noted that, when the anode portion is prepared by cutting a large sheet of metal foil, in order to provide a dielectric layer on the cut surface of the anode portion, the capacitor element in the state of the winding body can be further subjected to a chemical forming treatment.
[0067] As the electrolyte, an electrolytic solution or a solid electrolyte may be used, or a solid electrolyte and an electrolytic solution may be used in combination.
[0068] The solid electrolyte includes, for example, a manganese compound and a conductive polymer. As the conductive polymer, for example, polypyrrole, polythiophene, polyaniline and their derivatives can be used. The solid electrolyte including the conductive polymer can be formed, for example, by chemically polymerizing and / or electrolytically polymerizing the raw material monomer on the dielectric layer. Alternatively, it can be formed by applying a solution in which the conductive polymer is dissolved or a dispersion in which the conductive polymer is dispersed to the dielectric layer.
[0069] As the electrolyte, it can be a non-aqueous solvent, or a mixture of a non-aqueous solvent and an ionic substance (solute, such as an organic salt) dissolved therein. The non-aqueous solvent can be an organic solvent or an ionic liquid. As the non-aqueous solvent, for example, ethylene glycol, propylene glycol, cyclopentane, γ-butyrolactone, N-methylacetamide, etc. can be used. As the organic salt, for example, trimethylamine maleate, triethylamine borodisalicylate, ethyl dimethyl phthalate, 1,2,3,4-tetramethyl imidazolium phthalate, 1,3-dimethyl-2-ethyl imidazolium phthalate, etc. can be cited.
[0070] It should be noted that the power storage device is not limited to the electrolytic capacitor described in the present embodiment, as long as it is a device having a sealing member for sealing the outer shell. The power storage device having a sealing member includes various forms such as the following, that is, a battery including a secondary battery such as a lithium ion battery, a lithium ion polymer battery, a nickel-hydrogen battery, a lithium ion capacitor, and a double-layer capacitor.
[0071] [Example]
[0072] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples; however, the present invention is not limited to the following Examples.
[0073] 《Sample A1~A4》
[0074] In this sample, a wound electrolytic capacitor (diameter 10 mm×length 10 mm) having a rated voltage of 35 V and a rated capacitance of 270 μF was produced. A specific method for producing the electrolytic capacitor will be described below.
[0075] (Fabrication of capacitor elements)
[0076] The Al foil with a roughened surface is subjected to a chemical conversion treatment using an ammonium adipate solution to form a dielectric layer. The obtained anode portion is cut into a given size. Lead connectors are connected to the Al foils serving as the anode portion and the cathode portion, respectively, and the anode portion and the cathode portion are wound with a spacer sandwiched therebetween, and the outer surface is fixed with a winding fixing tape, thereby producing a wound body. At this time, the lead connector and the lead integrated with the lead connector are pulled out from the wound body, and the winding is performed while the lead connector is wound in. The wound body is further subjected to a chemical conversion treatment using an ammonium adipate solution again.
[0077] The wound body is immersed in a conductive polymer dispersion containing polyethylenedioxythiophene, polystyrene sulfonic acid and water contained in a given container for 5 minutes, and then the wound body is lifted from the conductive polymer dispersion. Then, the wound body impregnated with the polymer dispersion is dried in a drying oven at 150°C for 20 minutes to allow the conductive polymer to adhere between the anode and cathode parts of the wound body. The capacitor element is completed in this manner and contained in a bottomed cylindrical housing with a diameter of 10 mm and a length of 10 mm.
[0078] (Impermeation of electrolyte)
[0079] The electrolyte solution was injected into the case, and the electrolyte solution was impregnated into the capacitor element for 5 minutes in a reduced pressure atmosphere (40 kPa). The electrolyte solution was prepared by dissolving phthalic acid and triethylamine in a solvent containing γ-butyrolactone and ethylene glycol.
[0080] (Sealing of capacitor elements)
[0081] Lead terminals 15A and 15B extending from capacitor element 10 are inserted through Figure 1 The through hole 12a of the sealing member composed of the elastic member 12 is shown, and the leads 14A and 14B integrated with the lead tabs 15A and 15B are pulled out to the outside of the elastic member 12. In this state, the elastic member 12 is inserted into the opening of the housing 11, and the lateral drawing process is performed to fix the elastic member 12. The capacitor element 10 is sealed with the sealing member composed of the elastic member 12 by curling the opening end of the housing 11.
[0082] As the elastic member 12, a butyl polymer, a hindered phenol compound, a filler (calcined kaolin and talc), a crosslinking agent, and an additive are mixed and vulcanized into a disc-shaped member having a through hole 12a using a mold. As additives, a reinforcing agent (carbon black), a crosslinking accelerator, a dispersing aid (stearic acid) and a modifier (silane coupling agent) are used. It should be noted that, with respect to the amount of each component of the elastic member 12, the hindered phenol compound is set to 1.5 parts by mass, the calcined kaolin is set to 20 parts by mass, and the talc is set to 80 parts by mass, relative to 100 parts by mass of butyl rubber as an elastic polymer.
[0083] It should be noted that the hindered phenol compounds used in samples A1 to A4 are respectively the following (a1) to (a4). The heat of reaction Hr and molecular weight of phenol radical generation calculated according to the above-mentioned procedure are also described.
[0084] (a1) pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate], H r=76.8kcal / mol (≈321.3kJ / mol), molecular weight 1178
[0085] (a2) 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, H r =78.5kcal / mol (≈328.4kJ / mol), molecular weight 531
[0086] (a3) 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-mesitylene, H r =78.1kcal / mol (≈326.8kJ / mol), molecular weight 775
[0087] (a4) 1,3,5-tris[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, H r =80.0kcal / mol (≈334.7kJ / mol), molecular weight 784
[0088] In addition, the structural formulas of (a1) to (a4) are shown below.
[0089] [Chemistry 1]
[0090]
[0091] 《Samples B1 to B5》
[0092] An elastic member was formed in the same manner as in Sample A1 except that a less hindered phenol compound was used instead of the hindered phenol compound, and an electrolytic capacitor was produced using the elastic member.
[0093] The low hindered phenol compounds used in samples B1 to B5 are respectively the following (b1) to (b5). In these low hindered phenol compounds, as shown in the structural formulas (b1) to (b5), a hydrogen atom, a primary carbon, or a secondary carbon is bonded to at least one substitution position adjacent to the phenolic hydroxyl group in the phenol skeleton.
[0094] [Chemistry 2]
[0095]
[0096] The heat of reaction Hr and molecular weight of phenol radical generation calculated according to the above-mentioned procedures for (b1) to (b5) are as follows.
[0097] (b1)H r =83.0kcal / mol (≈347.3kJ / mol), molecular weight 545
[0098] (b2)H r =81.2kcal / mol (≈339.7kJ / mol), molecular weight 741
[0099] (b3)H r =83.2kcal / mol (≈348.1kJ / mol), molecular weight 369
[0100] (b4)H r =83.4 kcal / mol (≈348.9 kJ / mol), molecular weight 341
[0101] (b5)H r =83.3kcal / mol (≈348.5kJ / mol), molecular weight 407
[0102] "evaluate"
[0103] The thermal degradation of the elastic member was evaluated according to the following procedure.
[0104] (Evaluation 1)
[0105] The mass change rate of the elastic member produced in each of samples A and B was confirmed. The mass change rate was calculated from the initial mass m0 of the elastic member and the mass m1 after leaving it to stand for 500 hours in an environment of 165° C. according to the following formula.
[0106] Mass change rate (%) = ((m0-m1) / m0) × 100
[0107] (Rating 2)
[0108] The electrolytic capacitors of samples A and B were placed in an environment of 165°C for 500 hours, and the crack length of the elastic member was calculated. The crack length was calculated by measuring the straight-line distance between the two ends of the longest crack observed in the transmission photograph observed from the side of the electrolytic capacitor. Based on the crack length, the crack generation state was evaluated according to the following criteria.
[0109] ◎: Crack length is 0.2 mm or less.
[0110] ○: The crack length is greater than 0.2 mm and less than 0.7 mm.
[0111] △: Crack length is greater than 0.7 mm.
[0112] Table 1 shows the results.
[0113] [Table 1]
[0114] Quality change rate (%) Crack generation evaluation A1 3.5 ◎ A2 4.0 ◎ A3 4.3 ◎ A4 3.9 ◎ B1 8.2 △ B2 7.9 △ B3 8.0 △ B4 7.9 △ B5 8.2 △
[0115] 《Sample A5~A8》
[0116] The amounts of calcined kaolin and talc relative to 100 parts by mass of butyl rubber were changed as shown below. Elastic members and electrolytic capacitors were prepared and evaluated in the same manner as Sample A1 except for the above.
[0117] Calcined kaolin / talc=90 parts by mass / 10 parts by mass (A5), 70 parts by mass / 30 parts by mass (A6), 50 parts by mass / 50 parts by mass (A7), 0 parts by mass / 120 parts by mass (A8)
[0118] The results of samples A5 to A8 are shown in Table 2. Table 2 also shows the result of sample A1.
[0119] [Table 2]
[0120] Quality change rate (%) Crack generation evaluation A5 5.7 ○ A6 4.9 ◎ A7 4.3 ◎ A1 3.5 ◎ A8 2.9 ◎
[0121] 《Sample A9~A13》
[0122] Elastic members and electrolytic capacitors were prepared and evaluated in the same manner as samples A1 and A5 to A8 except that the amount of the hindered phenol compound was changed to 0.5 parts by mass based on 100 parts by mass of the butyl rubber. The amounts of calcined kaolin and talc were as follows.
[0123] Calcined kaolin / talc=90 parts by mass / 10 parts by mass (A9), 70 parts by mass / 30 parts by mass (A10), 50 parts by mass / 50 parts by mass (A11), 20 parts by mass / 80 parts by mass (A12), 0 parts by mass / 120 parts by mass (A13)
[0124] Table 3 shows the results of samples A9 to A13.
[0125] [Table 3]
[0126] Quality change rate (%) Crack generation evaluation A9 6.2 ○ A10 5.3 ○ A11 4.5 ◎ A12 3.6 ◎ A13 3.0 ◎
[0127] 《Samples A14 to A18》
[0128] Elastic members and electrolytic capacitors were prepared and evaluated in the same manner as samples A1 and A5 to A8 except that the amount of the hindered phenol compound was changed to 4.0 parts by mass based on 100 parts by mass of the butyl rubber. The amounts of calcined kaolin and talc were as follows.
[0129] Calcined kaolin / talc=90 parts by mass / 10 parts by mass (A14), 70 parts by mass / 30 parts by mass (A15), 50 parts by mass / 50 parts by mass (A16), 20 parts by mass / 80 parts by mass (A17), 0 parts by mass / 120 parts by mass (A18)
[0130] Table 4 shows the results of samples A14 to A18.
[0131] [Table 4]
[0132] Quality change rate (%) Crack generation evaluation A14 5.6 ○ A15 4.7 ◎ A16 4.1 ◎ A17 3.4 ◎ A18 2.7 ◎
[0133] 《Sample A19~A23》
[0134] Elastic members and electrolytic capacitors were prepared and evaluated in the same manner as samples A1 and A5 to A8 except that the amount of the hindered phenol compound was changed to 6.0 parts by mass based on 100 parts by mass of the butyl rubber. The amounts of calcined kaolin and talc were as follows.
[0135] Calcined kaolin / talc=90 parts by mass / 10 parts by mass (A19), 70 parts by mass / 30 parts by mass (A20), 50 parts by mass / 50 parts by mass (A21), 20 parts by mass / 80 parts by mass (A22), 0 parts by mass / 120 parts by mass (A23)
[0136] Table 5 shows the results of samples A19 to A23.
[0137] [Table 5]
[0138] Quality change rate (%) Crack generation evaluation A19 5.2 ○ A20 4.6 ◎ A21 4.0 ◎ A22 3.3 ◎ A23 2.5 ◎
[0139] As shown in Tables 2 to 5, even in Sample A to which talc was added, the mass change rate was low, the crack length was small, and the occurrence of cracks was reduced.
[0140] Industrial Applicability
[0141] In the electrolytic capacitor of the present invention, thermal degradation of the elastic member constituting the sealing member for sealing the opening of the housing is suppressed. Therefore, the electrolytic capacitor is suitable for use in applications such as use in an engine room of an automobile at high temperatures (eg, temperatures above 100° C. or 150° C.).
[0142] Explanation of symbols
[0143] 10 capacitor element, 11 housing, 11a reduced diameter region, 12 elastic member, 13 seat plate, 14A, 14B leads, 15A, 15B lead terminals, 21 anode portion, 22 cathode portion, 23 spacer, 24 winding fixing tape.
Claims
1. An electric storage device comprising an electric storage element, a case having an opening and accommodating the electric storage element, and a sealing member for sealing the opening, The sealing member includes an elastic member fitted into the opening. The elastic member comprises an elastic polymer and a hindered phenol compound, The hindered phenol compound has a first hindered group and a second hindered group at a first substitution position and a second substitution position adjacent to a phenolic hydroxyl group in a phenol skeleton, respectively. The first hindered group and the second hindered group each contain at least one tertiary carbon, With respect to the first hindered group and the second hindered group, one of the tertiary carbon atoms is bonded to the first substitution position and the second substitution position, respectively. The amount of the hindered phenol compound contained in the elastic member is 0.5 parts by mass or more and 6 parts by mass or less relative to 100 parts by mass of the elastic polymer. The hindered phenol compound has a molecular weight of 300 or more and 1500 or less.
2. The power storage device according to claim 1, wherein The elastic member further comprises talc, The amount of the talc contained in the elastic member is 50 parts by mass or more and 120 parts by mass or less relative to 100 parts by mass of the elastic polymer.
3. The power storage device according to claim 1, wherein The elastic member further comprises a filler, The filler further comprises talc, The total amount of the filler contained in the elastic member is 10 parts by mass or more and 120 parts by mass or less relative to 100 parts by mass of the elastic polymer. The amount of the talc contained in the elastic member is 10 parts by mass or more and 120 parts by mass or less relative to 100 parts by mass of the elastic polymer.
4. The power storage device according to claim 1, wherein The elastic member further comprises a filler, The filler comprises at least one selected from talc, mica, silica, kaolin, titanium dioxide and alumina, The total amount of talc, mica, silica, kaolin, titanium dioxide and alumina contained in the elastic member is 10 parts by mass or more and 120 parts by mass or less relative to 100 parts by mass of the elastic polymer. The amount of the talc contained in the elastic member is 10 parts by mass or more and 120 parts by mass or less relative to 100 parts by mass of the elastic polymer.
5. The power storage device according to claim 3 or 4, wherein: The amount of the talc contained in the elastic member is 50 parts by mass or more and 120 parts by mass or less relative to 100 parts by mass of the elastic polymer.
6. The power storage device according to any one of claims 1 to 4, wherein The elastic member has a through hole. The electric storage device includes a lead wire that passes through the through hole.
7. The power storage device according to any one of claims 1 to 4, wherein The housing has a region with a reduced diameter relative to a side wall of the elastic member.
8. The power storage device according to any one of claims 1 to 4, wherein The hindered phenol compound has a phenol free radical generation reaction heat of 82 kcal / mol or less.
9. The power storage device according to any one of claims 1 to 4, wherein: The first hindered group and the second hindered group are tert-butyl groups respectively.
10. The power storage device according to any one of claims 1 to 4, wherein The electric storage element is a capacitor element having an anode portion and a cathode portion, and the anode portion has a dielectric layer formed on a surface.
Citation Information
Patent Citations
Aluminum electrolytic capacitor
JP1999274011A
Aluminum electrolytic capacitor and method of producing the same
US20070165362A1